MAKNA KOMUNIKASI ANTARA PERAWAT DAN PASIEN PADA MASA ISOLASI PANDEMI COVID-19: (STUDI FENOMENOLOGI ANTARA PERAWAT DAN PASIEN PADA MASA ISOLASI COVID-19 DI KAB. GARUT) - Rosanti Utami Dewi Suyatman Yatnosaputro (Prodi Ilmu Komunikasi Universitas Putera Batam, 2023)
This research is motivated by the many cases of people exposed to Covid-19 who have to carry out isolation. With an increase in positive Covid-19 patients with a very fast risk of transmission, so in this study how to communicate patients and nurses in interpreting them during isolation during a pandemic. This study uses a qualitative approach with phenomenology theory which has the basic assumption that humans actively interpret the experiences they feel by giving meaning to something they have experienced. Data collection techniques used are observation, in-depth interviews and literature study. There were 6 informants in this study including Covid-19 patients and nurses and 3 informants from hospitals, the Health Service and the Covid-19 Task Force. The results of the study showed that the motives of patients and nurses during the isolation period had motives to help heal Covid-19 patients and for patients to have motives to cure Covid-19 by isolating in hospitals, and motives because this is how patients and nurses can become part of Covid -19. Initially, patients with Covid-19 experienced transmission from those infected with Covid-19. In the process of isolation to divert fear. Experiences felt by patients and nurses get positive and negative experiences during isolation. This is the experience experienced by the informant who hopes that the Covid-19 pandemic will end quickly because they are tired enough to face this pandemic and it is hoped that a pandemic like this will not happen again. keywords: phenomenology, isolation, covid-19, experience